Korelasi Antara Dakwah Kultural Dalam Tafsir Al-Ibrīz Dan Konsep Humanisasi Dalam Pendidikan Agama Islam - Uswatun Khasanah Khasanah; Enjang Burhanudin Yusuf (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research deeply analyzes the functional and substantial correlation between Cultural Da'wah (Da’wah Kultural) as internalized in Tafsir Al-Ibrīz by K.H. Bisri Musthofa and the Humanization Concept in Islamic Religious Education (PAI). Tafsir Al-Ibrīz is a masterpiece of tafsīr bi al-ra’yi written in Javanese Pegon script, reflecting an adaptive, inclusive, and highly contextual da'wah approach to Javanese culture (Musthofa, 2011). This approach is essentially a practice of sharī'ah humanization that prioritizes taysīr (facilitation) and raf’u al-ḥaraj (avoiding hardship), aligning perfectly with the principles of Nusantara Islam (Wahid, 2006). The Humanization Concept in PAI, conversely, focuses on developing human dignity (karāmah insāniyyah), critical reasoning, and rejecting dogmatic and authoritarian teaching methods (Misrawi, 2010; Freire, 2103). Using qualitative content analysis and comparative methods, this study identifies three main correlation points: (1) Contextualization of Language and Locality (X1), (2) Dialogical and Empathetic Methodology (Ukhuwwah) (X3), and (3) The Ethical Goal of Tolerant Insān Kāmil (Y3). The results demonstrate a positive and significant correlation (r = 0.89) between variable X (Cultural Da’wah of Al-Ibrīz) and variable Y (Humanization Principles of PAI). This correlation proves that Tafsir Al-Ibrīz is a rich pedagogical prototype for designing a humanistic, inclusive PAI curriculum capable of responding to the challenges of radicalism while upholding universal humanitarian values.